Conventional Soil Management May Promote Nutrients That Lure an Insect Pest to a Toxic Crop. Issue 2 (30th December 2020) - Schmidt-Jeffris, Rebecca A; Moretti, Erica A; Wickings, Kyle; Wolfin, Michael S; Northfield, Tobin D; Linn, Charlie E; Nault, Brian A
Abstract: Slow and consistent nutrient release by organic fertilizers can improve plant nutrient balance and defenses, leading to herbivore avoidance of organically managed crops in favor of conventional crops with weaker defenses. We propose that this relative attraction to conventional plants, coupled with the use of genetically modified, insecticidal crops ( Bt ), has created an unintentional attract-and-kill system. We sought to determine whether Bt and non- Bt corn Zea mays L. plants grown in soil collected from five paired organic and conventional fields differed in attractiveness to European corn borer [ Ostrinia nubilalis (Hübner)] moths, by conducting ovipositional choice and flight tunnel assays. We then examined the mechanisms driving the observed differences in attraction by comparing soil nutrient profiles, soil microbial activity, plant nutrition, and plant volatile profiles. Finally, we assessed whether European corn borer abundance near corn fields differed based on soil management. European corn borer preferred plants grown in conventional soil but did not discriminate between Bt and non- Bt corn. Organic management and more alkaline soil were associated with an increased soil magnesium:potassium ratio, which increased plant magnesium, and were linked to reduced European corn borer oviposition. There was an inconsistent trend for higher European corn borer moth activity near conventional fields. Our results extend the mineral balance hypothesis describing conventional plant preference by showing that it can also improve attraction to plants with genetically inserted toxins. Unintentional attract (to conventional) and ( Bt ) kill is a plausible scenario for pest declines in response to Bt corn adoption, but this effect may be obscured by variation in other management practices and landscape characteristics. Graphical Abstract: